Dampak Kenaikan PPn Terhadap Ekonomi dan Kesejahteraan Masyarakat - Lamsah, Lamsah (Media Akuntansi Perpajakan, 2025)
The purpose of this research is to analyze the impact of the increase in Value Added Tax (VAT) on macroeconomic conditions and the level of public welfare in Indonesia.The increase in PPn as part of the government's strategy to increase state revenues, this has various implications, both for people's purchasing power and for business actors. This study uses a qualitative approach. The results of the study indicate that the increase in PPn tends to increase the burden of public consumption, especially the lower middle income group, which in turn can reduce the level of welfare. From a macroeconomic perspective, although state revenues increase, there is a risk of a decline in domestic consumption growth which has an impact on slowing short-term economic growth. This study recommends that the PPn increase policy be balanced with a targeted compensation program to minimize the negative impact on vulnerable communities and maintain national economic stability.